Adoption of Digital Banking in Nepal: An Analysis of Customer Perceptions and Behaviors - Kandel, Madan; Timilsina, Jagat; Basnet, Bhupindra Jung; Joshi, Ramesh Dutta (NPRC Journal of Multidisciplinary Research, 2024)
Digital banking is reshaping the financial landscape worldwide, offering substantial opportunities for developing economies like Nepal. This study investigates the factors influencing digital banking adoption in Nepal, emphasizing customer perceptions, demographic characteristics, and behavioral patterns. The research aimed to assess the extent of digital banking adoption, identify the key determinants driving its usage, and explore the relationship between these factors and user behavior. A sample of 380 respondents, representing diverse demographic and geographical segments, participated in the study. Data were collected through structured questionnaires and analyzed using descriptive statistics, correlation, and multiple regression techniques. The findings reveal that perceived ease of use (PEOU) is the most significant predictor of adoption (03b2 = 0.766, p < 0.01), followed by convenience (03b2 = 0.346), perceived credibility (03b2 = 0.287), and perceived usefulness (03b2 = 0.268). Demographic insights indicate that middle-aged, educated, and professionally engaged individuals are the primary users of digital banking, with weekly interaction (44.5%) being the most common usage pattern. The study highlights the importance of user-friendly platforms, robust security measures, and targeted educational initiatives to promote widespread adoption. Policymakers can leverage these findings to develop inclusive regulations, while financial institutions are encouraged to innovate continually to align with evolving customer expectations. By addressing key challenges, this research provides actionable strategies to enhance digital banking adoption in Nepal, contributing to the broader literature on digital transformation in developing economies.